2005
DOI: 10.1083/jcb.200408188
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cytoplasmic residues of Sec61p involved in ribosome binding and cotranslational translocation

Abstract: The cytoplasmic surface of Sec61p is the binding site for the ribosome and has been proposed to interact with the signal recognition particle receptor during targeting of the ribosome nascent chain complex to the translocation channel. Point mutations in cytoplasmic loops six (L6) and eight (L8) of yeast Sec61p cause reductions in growth rates and defects in the translocation of nascent polypeptides that use the cotranslational translocation pathway. Sec61 heterotrimers isolated from the L8 sec61 mutants have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
123
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(134 citation statements)
references
References 45 publications
11
123
0
Order By: Relevance
“…Since C5 is located in the C-terminal domain and TMS4c in the N-terminal domain of SecY, a simultaneous interaction of inserted SecA with both interaction sites (green in Figure 6) could induce the outward directed force on each domain that is required for their separation. A similar mechanism could underlie the ribosome induced opening mechanism as well, as the ribosome also interacts with the C5 loop 37 and with the cytoplasmic domain of SecG which is bound to the Nterminal domain of SecY. 14 Taken together, our studies provide the first demonstration of two SecY regions that interact with SecA, including a region where SecA possibly inserts into the SecYEG channel.…”
Section: Discussionmentioning
confidence: 55%
“…Since C5 is located in the C-terminal domain and TMS4c in the N-terminal domain of SecY, a simultaneous interaction of inserted SecA with both interaction sites (green in Figure 6) could induce the outward directed force on each domain that is required for their separation. A similar mechanism could underlie the ribosome induced opening mechanism as well, as the ribosome also interacts with the C5 loop 37 and with the cytoplasmic domain of SecG which is bound to the Nterminal domain of SecY. 14 Taken together, our studies provide the first demonstration of two SecY regions that interact with SecA, including a region where SecA possibly inserts into the SecYEG channel.…”
Section: Discussionmentioning
confidence: 55%
“…K, proteinase K. more than one TM domain SecA can access the hydrophilic domain in the presence of the ribosome. Although the exact contact sites between the bacterial SecY translocon and the ribosome have yet to be mapped, extensive studies on the homologous eukaryotic Sec61 channel have indicated that RNC binding occurs at the cytoplasmic loop connecting TM8 and TM9 domains and at the C-terminal tail of Sec61 (50,51). These domains are surface-exposed in the x-ray structure of the bacterial SecY and are also suggested to be involved in SecA binding (52).…”
Section: Discussionmentioning
confidence: 99%
“…The ribosome binding site in Sec61p has been identified in cytosolic loop 8 (Kalies et al, 2005;Cheng et al, 2005). We therefore asked, whether a mutation in this loop, sec61R406E, which has been shown to drastically lower the affinity of ribosomes for the Sec61 channel, had any effect on proteasome binding to ER membranes (Fig.…”
Section: Proteasomes and Ribosomes Bind To Different Sites In The Secmentioning
confidence: 99%
“…This channel on its own mediates cotranslational protein translocation into the ER, during which the ribosome binds to Sec61p and Sbh1p (Kalies et al, 2005;Levy et al, 2001). A mutation in the cytosolic loop 8 of Sec61p reduces its affinity for ribosomes (Cheng et al, 2005). The crystal structure of an archaeal homologous channel in the closed conformation consists of a single Sec61␣/␤/␥ heterotrimer, but the presence of ribosome-nascent chain complexes with signal peptides provokes the assembly of three to four heterotrimers in the ER membrane which can also be co-isolated with ribosomes from ER membranes and fluorescence quenching experiments suggest that in the open state the channel is formed by several Sec61 complexes (van den Berg et al, 2004;Hanein et al, 1996;Hamman et al, 1997).…”
Section: Introductionmentioning
confidence: 99%